Access, security and diplomacy: Perceptions of soft power, nation branding and the organisational challenges facing Qatar's 2022 FIFA World Cup. Issue 1 (17th May 2019) - Rookwood, Joel
Abstract : Purpose: The purpose of this paper is to focus on the perceptions of Qatar's suitability to act a successful sports event host and, in doing so, look ahead to some of the key organisational challenges facing Qatar leading up to the World Cup in 2022. This paper is framed around the perceptions of nation branding and soft power and draws on the experiences of various key demographics who offer valuable insight into Qatar's World Cup. Design/methodology/approach: Semi-structured interviews were conducted with football journalists, experienced tournament staff and volunteers, football supporters and expatriates working in the Gulf region. The paper is longitudinal in nature, with data collected between January 2010 and June 2018 including seven FIFA and FIFA-affiliated confederation events, namely, the 2011 Asia Cup in Qatar, the 2011 Gold Cup in USA, the 2014 World Cup in Brazil, the 2015 Copa America in Chile, the 2016 European Championships in France, the 2017 African Cup of Nations in Gabon and the 2018 World Cup in Russia. Findings: The paper uncovers several concerns and considerations connected to hosting a first Middle Eastern World Cup in Qatar in 2022. The findings demonstrate some of the key organisational challenges facing the event which were found to include supporter access, security and the fan experience. Originality/value: This paper examines Qatar in the context of the 2022 World Cup and its connection to soft power and nation branding. This particular event is so significant, not simply because it is the showcase tournament of the globe's most popular sport from both a spectator and participation perspective, but because it represents such a notable divergence from previous editions. The majority of preceding World Cups have/will be hosted by highly populated countries with relatively developed football traditions and/or infrastructures. As a change to this pattern, the unique position of Qatar's World Cup renders it as an important case study. This paper, which examines informed perspectives relating to access, security and diplomacy, provides a number of issues for Qatar's World Cup organisers to consider.